Pengembangan Media Pembelajaran Video Animasi Materi Tata Surya Pada Muatan IPA di Kelas VI Sekolah Dasar Muhammadiyah 06 Tebet Jakarta - Yuli Pindy Ikasari; Febrianti Yuli Satriyani (Universitas Negeri Padang, 2022)
The purpose of this research is to produce animated video learning media that is theoretically valid and effective in achieving learning objectives. This research includes development research. This study uses a simplified development model from Borg&Gall which includes: (1) potential problems, (2) data collection, (3) product development planning, (4) internal design testing, (5) design revision, (6) limited trial, and (7) main field trials. The instrument used is a questionnaire while the data analysis used is a Likert Scale. The results of the research that the animated video media developed has a very valid value, obtained 100% achievement percentage from media expert validators, 95% achievement percentage from material expert validators and very effective with 89% achievement percentage to achieve learning objectives on Solar System material in class VI SDS Muhammadiyah 06 Tebet Jakarta